Answer:
x = -2
y = -23
(x, y) --> ( -2, -23)
Explanation:
y = 6x - 11
-2x - 3y = -7
***What you need to do is substitute the "y" with what has been given to us which is "6x - 11"***
-2x - 3(6x - 11) = -7
Now what you need to do, is use the distributive property (multiply what is in the parenthesis "6x - 11" by what is outside of it "3").
-3 × 6x and -3 × -11
-18x and 33
Now we have......
-2x - 18x + 33 = -7
Now we can combine like terms (put the numbers that are the same together - variables with variables, and whole numbers with whole numbers)
-2x - 18x = -20x (2 negatives added together gives u a result of a bigger negative number)
-20x + 33 = -7
Now we need to subtract 33 on both sides
-20x + 33 - 33 = -7 - 33
-20x = -40
Now we need to divide by -20 on both sides to isolate the variable
-20x ÷ -20 = -40 ÷ 20
x = -2
Now that we have what "x" is, we can use that to find what "y" is....
y = 6x - 11
Substitute the "x" with the answer we got "-2".
y = 6(-2) - 11
y = -12 - 11
y = -23
x = -2
y = -23
Now we can check our work
y = 6x - 11
All we need to do is substitute the "x" and "y" with the answer we got above.
y = 6x - 11
-23 = 6(-2) - 11
-23 = -12 - 11
-23 = -23
CORRECT
So now that we checked our work, and saw that it was correct, I can hereby say that x is -2 and y is -23
x = -2
y = -23
(x, y) --> ( -2, -23)
Hope this helped!!!